2009
DOI: 10.1590/s1519-69842009000300018
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton diversity in the Upper Paraná River floodplain during two years of drought (2000 and 2001)

Abstract: Floodplain lakes and lotic environments of the High Paraná River floodplain present notable biodiversity, especially in relation to phytoplanktonic community. The goal of this work was to evaluate phytoplankton diversity (alpha, beta and gamma) in three subsystems during two years of drought (2000 and 2001). We sampled 33 habitats at the pelagic zone subsurface during February and August. Due to low hydrometric levels of the Paraná and Ivinhema Rivers, there was no clear distinction between the potamophase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 17 publications
(23 reference statements)
4
32
1
Order By: Relevance
“…Other conditions for the development of phytoplankton in the summer have been reported, such as increased temperature and luminosity (Salmaso and Zignin 2010). In general, the low values of algal biomass recorded in the studied streams are in agreement with the mean values observed in other stream ecosystems (Soares et al 2007, Borges and Train 2009, Kireta et al 2012.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Other conditions for the development of phytoplankton in the summer have been reported, such as increased temperature and luminosity (Salmaso and Zignin 2010). In general, the low values of algal biomass recorded in the studied streams are in agreement with the mean values observed in other stream ecosystems (Soares et al 2007, Borges and Train 2009, Kireta et al 2012.…”
Section: Discussionsupporting
confidence: 89%
“…Many studies in stream ecosystems have showed seasonality as the main variable correlated with higher values of algal biomass, chlorophyll-a and species richness (Rodrigues et al 2007, Borges and Train 2009, Rossetti et al 2009, Tavernini et al 2011. In the present study, the higher rainfall recorded during the summer might be the explanation for the higher biomass and diversity observed in the studied streams.…”
Section: Discussionsupporting
confidence: 59%
“…studied the Paraibuna and Pomba River and recorded a dominance of diatoms and desmids in the biovolume in the middle and downstream stretch of Pomba River. Train and Rodrigues (1998) and Train et al (2000) recorded the dominance of cyanobacteria in the biovolume of the Baía River, as well as in a side canal of the Alto Paraná River.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that cover lotic portions in the area of the Paraná River basin focusing on ecological studies of the phytoplankton community are still rare, considering the area size and the large number of tributaries: Bonetto et al (1979Bonetto et al ( , 1982, Garcia de Emiliani (1988, 1990, Henry et al (1998), O'Farrell et al (1996), Train and Rodrigues (1998), Train et al (2000), Borges et al (2003), Ferrareze and Nogueira (2006), Rodrigues et al (2009), Borges and Train (2009) and Perbiche-Neves et al (2011).…”
Section: Introductionmentioning
confidence: 99%
“…Meroplanktonic diatoms such as Aulacoseira spp. have life cycles closely related to the mixing of the water column (Lund, 1965) and are common components of the plankton in turbulent environments (Nogueira, 2000;Bovo-Scomparin and Train, 2008;Rodrigues et al, 2009;Borges and Train, 2009).…”
Section: Discussionmentioning
confidence: 99%